Obstructive Sleep Apnea (OSA) pada Usia Produktif - Annisarahma, Lyvia; Karima, Nisa; Sangging, Putu Ristyaning Ayu; Rudiyanto, Waluyo (CV. Jasa Sukses Abadi, 2024)
Obstructive sleep apnea (OSA) is a sleep disorder which characterized by cessation of breathing for more than 10 seconds. A blockage in the upper respiratory tract may be the cause of OSA. One known risk factor for OSA is smoking. Moreover, the degree of physical activity might also influence OSA risk. This article is a literature review with a variety of the latest sources that are relevant to the topic. The sources used were obtained from the search engine for health journals. The prevalence of OSA in the productive age community in Asia is 4.1 - 7.5%. Some factors that affect the symptoms of OSA, especially in productive age, namely obesity, male sex, old age, genetic, smoking habits, and small upper airway diameter. OSA is characterized by snoring, periodic apnea, hypoxemia during sleep and hypersomnolence during the day. Some symptoms of OSA are snoring hard and annoying, stopping repeated breathing during sleep at night, insomnia, fatigue, and drowsiness during the day. Death from OSA in productive age is usually caused by complications after having OSA in the long period ahead.